Anteseden yang Mempengaruhi Repurchase Intention Konsumen pada Smartphone Buatan Korea - Al Fajri, Faiz; Bagaskara, Bima; Marlina Wijayanti, Ranni; Berlinda Christi, Yosephine; Suhud, Usep (Jurnal Bisnis, Manajemen, dan Keuangan, 2020)
This study aims to examine the factors that influence the repurchase intention of Korean mobile consumers. In this study, there are four variables used to measure repurchase intention, namely perceived quality, perceived value, brand equity, and customer satisfaction. Data collection was taken out randomly from April to May 2020. Data was collected through a survey by distributing online questionnaires selected using purposive sampling techniques. The total respondents in this study were 250 people consisting of 44 men and 206 women who had and were using mobile phones made in Korea. Data were processed using exploratory factor analysis and structural equation models. The results of this study are the variable perceived quality, perceived value, brand equity, and customer satisfaction have a positive and significant effect on repurchase intention.